The Vertıcal Changes Of Ortodontıc Area Wıth Treatment And Retentıon In Extractıon Cases - Oktay Üner; Müfide Dinçer (Galenos Yayinevi, 1989)
The purpose of this study is to determine the vertical changes of orthodontic area during active orthodontic treatment and retention. 10 subjects with Angle class I malocclusion having mean skeletal age of 14 years 3 months were examined. After extraction of first premolars, orthodontic treatments were performed at a mean period of 17.6 months by using "Modified Edgewise Technique"; the Hawley Retainers were used during the retention period for 16.8 months after the active orthodontic treatment. 10 subjects with normal occlusion having mean age 13 years 11 months and 10 subjects with normal occlusion having mean age 15 years 6 months were separeted as control groups. On the tracings of cephalometric radiographs, the measurements relating to vertical dimensions were made. The mean values of these measurements were calculates and statistically evaluated. During the active orthodontics treatment the increases in anterior and posterior vertical dimensions; the extrusions in lower, upper first molars and upper incisor were found. Similarly, the increases in anterior and posterior vertical dimensions, the extrusions upper molars and incisors were found in retention period. It has been indicated that changes in vertical dimensions are more likely resulting from the growth rather than the treatment effects.